2012
DOI: 10.1115/1.4006318
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of Tip Clearance and Bleed Effects in a Centrifugal Compressor Stage With Pipe Diffuser

Abstract: The subject of this paper is the experimental and numerical investigation of a state-of-the-art high pressure centrifugal compressor stage with pipe diffuser for a jet engine application. This study shows the impact of impeller tip clearance- and bleed-variation on the centrifugal stage. The purpose of this paper is threefold. In the first place, it investigates the effects on the stage performance. Secondly, it seeks to explain local flow-phenomena, especially in the diffuser. Finally, it shows that steady CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 4 publications
0
9
1
Order By: Relevance
“…Similarly, when the reverse flow caused by the impeller passes through the ridge of the pipe diffuser near the shroud, a vortex is formed at the shroud/suction side region. This is different from the results shown in the previous studies, [1][2][3] where just two vortices were found induced by scallop leading edge of pipe diffuser. As the fluid convects along the pipe passage, these three vortices are enhanced until the throat at Plane III.…”
Section: Flow Mechanism In Various Diffuserscontrasting
confidence: 99%
See 3 more Smart Citations
“…Similarly, when the reverse flow caused by the impeller passes through the ridge of the pipe diffuser near the shroud, a vortex is formed at the shroud/suction side region. This is different from the results shown in the previous studies, [1][2][3] where just two vortices were found induced by scallop leading edge of pipe diffuser. As the fluid convects along the pipe passage, these three vortices are enhanced until the throat at Plane III.…”
Section: Flow Mechanism In Various Diffuserscontrasting
confidence: 99%
“…This configuration is normally employed by General Electric. [1][2][3][4][5]10 As shown in Figure 2, at the throat of the pipe diffuser, the cross section is circular, and then the cross section becomes oblong with semi-circular ends attached by straight lines, like an oval along a straight centerline. The long axis of the cross section gradually increases, whereas the short axis and semicircular radius are equal to the diffuser throat diameter along a straight centerline.…”
Section: Configuration Amentioning
confidence: 99%
See 2 more Smart Citations
“…The impeller deformation and adjusted tip clearance was claimed to influence the aerodynamic performance and structure reliability of the compressor system. Kunte and Schwarz [35] have investigated the tip clearance and bleed effect, based on a centrifugal compressor stage. Experimental data were gathered and compared with CFD results from TRACE, which was developed by DLR.…”
Section: Tip Clearance Effectmentioning
confidence: 99%